Gender differences in textism features among university students - Ahmad Zukhi, Qurratull Aini; Ariffin, Adlina (AMCS Press, 2022)
This research highlights the differences of texting behaviour shown by male and female university students. Textism features consist of interesting characteristics used in text messaging such as abbreviations, emojis, stickers and GIF (Graphic Interchange Format). This study was conducted to analyse the usage of abbreviation and emojis among male and female students. The study was conducted on male and female university students aged from 19 to 25 years old through Google Form that acts as a replication of texting applications such as WhatsApp and Telegram messenger. It was found that male students prefer to reply in a simple form compared to female students. Moreover, there were five additional new features identified in the study which were added letters, Malay stylisation, double words, missing space and expression-based spellings. Besides, in terms of the differences of emojis used, female students applied wider types of emojis compared to male students.